2005
DOI: 10.1007/s11095-005-6157-8
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-EC-Guanine: Synthesis, Biodistribution, and Tumor Imaging in Animals

Abstract: Our results indicate that (99m)Tc-EC-Guan may be useful as a tumor proliferation imaging agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Ethylenedicysteine (EC) is the most recent and successful example of N 2 S 2 chelates (1821). EC can be labeled with metallic isotopes easily and efficiently with high radiochemical purity and stability (1214).…”
Section: Discussionmentioning
confidence: 99%
“…Ethylenedicysteine (EC) is the most recent and successful example of N 2 S 2 chelates (1821). EC can be labeled with metallic isotopes easily and efficiently with high radiochemical purity and stability (1214).…”
Section: Discussionmentioning
confidence: 99%
“…9). 158 Cell culture assays indicated that EC-Guan was incorporated in DNA, and there was no significant uptake difference between HSVTK overexpressed and normal groups. Biodistribution and scintigraphic imaging studies of 99m Tc-EC-Guanine showed increased tumor/tissue count density ratios as a function of time.…”
Section: Radiolabeled Nucleosidementioning
confidence: 94%
“…Thus, researchers reported that future quantitative studies will be needed to understand using these radiolabeled agents for imaging HSV1-tk reporter gene expression with PET [15]. Yang et al [16] synthesized 99m Tcethylenedicysteine-guanine ( 99m Tc-EC-Guan) and evaluated its cell proliferation selecting A-549, ovarian OCA-3, PC-3 and HSV-tk gene transfected PC-3 cancer cell lines. They reported that there was no significant uptake difference between HSV-TK over expressed and normal groups.…”
Section: Cell Culturementioning
confidence: 99%